Reduced Expression of Chl1 gene Impairs Insulin Secretion by Down-Regulating the Expression of Key Molecules of β-cell Function - Taneera, Jalal; Dhaiban, Sarah; Hachim, Mahmood; Mohammed, Abdul Khader; Mukhopadhyay, Debasmita; Bajbouj, Khuloud; Hamoudi, Rifat; Salehi, Albert; Hamad, Mawieh (Experimental and Clinical Endocrinology & Diabetes, 2019)
Silencing of Chl1 gene expression has been previously reported to reduce insulin secretion. Nevertheless, the mechanism underlying this effect remains unclear. In this study, we performed a serial of studies to investigate how Chl1 affects insulin secretion in INS-1 cells. RNA-sequencing was used to investigate the expression of CHL1 in human adipose, liver, muscle, and human islets. Silencing of Chl1 in INS-1 cells was done to assess its impact on the insulin secretion, content, cell viability, and apoptosis. In addition, gene set enrichment analysis (GSEA) was performed to identify possible molecular signatures that associate with Chl1 expression silencing.RNA sequencing data revealed a high expression of CHL1 in pancreatic islets and adipose tissues compared to liver and muscles tissues. Diabetic islets exhibited a lower expression of CHL1 as compared to non-diabetic islets. CHL1 expression was found to correlate positively with insulin secretory index, GLP1R but inversely with HbA1c and BMI. Silencing of Chl1 in INS-1 cells markedly reduced insulin content and secretion. The expression of key molecules of β-cell function including Insulin, Pdx1, Gck, Glut2, and Insrβ was down-regulated in Chl1-silenced cells at transcriptional and translational levels. Cell viability, apoptosis, and proliferation rate were not affected. GSEA showed that the insulin-signaling pathway was influenced in Chl1-silenced cells. Silencing of Chl1 impairs β-cell function by disrupting the activity of key signaling pathways of importance for insulin biosynthesis and secretion.
Keywords: diabetes; insulin secretion; Chl1; INS-1 (832/31); gene expression microarray; human islets; GSEA.